Analisis Pengaruh Capital Adequacy Ratio (CAR) dan Financing to Deposit Ratio (FDR) terhadap Return On Asset (ROA) dan Return On Equity (ROE) Pada Perusahaan Bank Umum Syariah di Indonesia - Nur Rahmadi (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
This research performed aims to review test the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) against the Return On Asset (ROA) and Return On Equity (ROE) with Corporate Commercial Bank Syariah Registered in Bank Indonesia as samples method with purposive sampling. Analysis techniques used with method of multiple linear regression, Analyst influence CAR And FDR against ROA, and the effect of CAR and FDR against ROE over the period 2011-2015. Results showed that operates simultaneously Singer Model at first variable ROA and ROA against FDR significant influence p-value 0.006 <0.005. Model while on both ROA and ROE. FDR significant effect against 0.006 p-value <0.005. First partial operating variables Model in CAR has a significant influence Against Its ROA with p-value 0.004 <0.05 and FDR had a significant influence Against Its ROA with p-value 0.003 <0.05. Model while the CAR both variables have a significant influence against The ROE with p-value 0.000 <0.05 and FDR had a significant influence against The ROE with p-value 0.001 <0.05.